(untitled) (The Journal of Nuwakot Adarsha Multiple Campus, 2025)
This article discusses how the media helps to the society for dealing with disasters management in Nepal. This study has based on an analysis of the secondary sources of information. It highlights the media’s role for empowering the society which is proactively educating the public about the disasters. In times of crisis management, accurate information on high-quality necessary resources like medicine and the media is an essential tool before, during, and after the disaster. During the risk, preparedness, recovery and response phases of disaster management, the media must be proactive, active and post-active as a form of preparedness, preparedness and post-preparedness by using the proper communication channels as a media to aware the people on disaster related activities. This paper explores the critical role of media in disaster management, crisis communication, and social transformation, with a particular focus on Nepal. It examines how media functioned during the COVID-19 pandemic and the 2015 Gorkha earthquake, highlighting its strengths in raising awareness and informing the public, as well as its weaknesses in maintaining consistent, accurate, and ethical reporting. The discussion integrates theoretical perspectives such as Functional Theory and Media Dependency Theory to analyze media responsibilities in times of crisis. Challenges such as political influence, misinformation, lack of professionalism, and inadequate government support are identified as barriers to effective media performance. While media freedom is essential in democratic societies, this freedom must be exercised with accountability. The paper argues that ethical journalism, combined with responsible regulation and institutional support, is vital for ensuring media fulfills its role as a voice for the people and a driver of positive societal change